Pelvic floor muscle training: mechanisms of action for the improvement of genitourinary syndrome of menopause. (2nd September 2020) - Mercier, J.; Morin, M.; Tang, A.; Reichetzer, B.; Lemieux, M.-C.; Samir, K.; Zaki, D.; Gougeon, F.; Dumoulin, C.
Abstract: Objective: This study aims to investigate the mechanism of action of pelvic floor muscle training (PFMT) for the improvement of the signs and symptoms of genitourinary syndrome of menopause (GSM) in postmenopausal women with GSM and urinary incontinence (UI). Methods: Twenty-nine women were included in the secondary analysis of a single-arm feasibility study. Using color Doppler ultrasound, the peak systolic velocity, time-averaged maximum velocity, and pulsatility index of the internal pudendal and dorsal clitoral arteries were measured at rest and after a pelvic floor muscle (PFM) contraction task. PFM function was assessed by dynamometry, and vulvovaginal tissue elasticity was measured using the Vaginal Atrophy Index. Results: PFMT significantly improved blood flow parameters in both arteries ( p  < 0.05) and significantly increased the speed of PFM relaxation after a contraction ( p  = 0.003). After the intervention, a marginally significant decrease in PFM tone was observed, as well as an increase in PFM strength ( p  = 0.060 and p  = 0.051, respectively). Finally, improvements in skin elasticity and introitus width were observed as measured by the Vaginal Atrophy Index ( p  < 0.007). Conclusion: Our findings suggest that PFMT improves blood flow in vulvovaginal tissues, PFM relaxation capacity, and vulvovaginal tissue elasticity in postmenopausal women with GSM and UI.